Manajemen Keuangan Pada UMKM Budidaya Jangrik Dan Dimsum Di Pondok Benda Pamulang Tangerang Selatan - AR, Rasmawati; Hakim, Melati Puspita; Sitohang, Rony Marthin (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2024)
Financial management includes aspects of budget planning, cash flow management, debt and credit management, investment, accurate financial analysis, control and monitoring of a business's financial resources. With good financial management, MSMEs can avoid liquidation problems, minimize financial risks and make the right business decisions. However, not all MSMEs are able to carry out good financial management and comply with applicable standards. The MSMEs that Mr. Jhandriansyah runs with two types of business, namely cricket cultivation and dimsum production, of course have a financial management system to be able to exist in both types of business. The aim of this research is to find out what the financial management system is that is applied to Mr. Jhandriansyah's cricket and dimsum cultivation MSMEs in Pondok. Benda Pamulang South Tangerang has met good financial management standards. Qualitative descriptive research method using data analysis techniques through 4 financial management indicators consisting of financial planning, recording, reporting and financial control. The data used is primary data where all data is obtained directly from the owner as the main informant. Data collection techniques using interviews, observation and literature study. The results of the research show that the understanding and application of Jhandriansyah's Cricket and Dimsum Cultivation MSMEs towards financial planning, reporting and control does not fully meet the principles of good financial management. This is because the owner of the Cricket and Dimsum Cultivation UMKM believes that the business currently being managed is still relatively small and can still be managed with simple financial management procedures where the 4 indicators can still be carried out by the owner himself according to understanding, experience and conditions in the field